Transferring Oncidium novaesae to Gomesa (Orchidaceae) and notes on Gomesa doeringii - de Fraga, C. N.; Fontana, A. P. (Phytotaxa, 2011)
The study of the Augusto Ruschi type materials currently deposited in the Museu de Biologia Prof. Mello Leitao, in Santa Teresa, Espirito Santo State, Brazil, makes it possible to recognise a historically neglected, but validly published species, Oncidium novaesae, which is here transferred to Gomesa, with designation of a lectotype and indication of synonymy. In addition, a superfluous combination in Gomesa is identified.